(untitled) (Journal of Rangpur Medical College, 2025)
Background: Bronchiolitis, a common lower respiratory tract infection in infants, is primarily caused by respiratory syncytial virus (RSV). Management typically includes supportive care with oxygen therapy, hydration, and sometimes bronchodilators. However, the efficacy of bronchodilators remains debated. Objective: The study aimed to compare the effectiveness of nebulized ipratropium bromide and salbutamol in treating acute bronchiolitis in infants. Methods: An open-label, cross-sectional study was conducted at Chittagong Medical College Hospital from October 2008 to September 2009. Infants aged 2-12 months, presenting with their first episode of respiratory distress and clinical signs of viral respiratory illness (temperature ≥38°C and/or coryza), were included. The two groups (salbutamol and ipratropium bromide) were assessed at baseline and at 12, 24, 36, and 48 hours using the Modified Respiratory Distress Assessment Instrument (MRDAI) score. Clinical outcomes, including changes in MRDAI scores,drug side effects, and hospital length of stay (LOS), were recorded. Results: The study found no significant differences in MRDAI scores, LOS, or adverse effects between the two groups. Both salbutamol and ipratropium bromide were effective in relieving symptoms of acute bronchiolitis. Conclusion: Nebulized salbutamol and ipratropium bromide are equally effective in managing acute bronchiolitis in infants. J Rang Med Col. March 2025; Vol.10, No.1: 40-44